A Highway through the Wood: Translation as a Colonial Venture in Nineteenth-Century Bengal (Erothanatos: A Peer-Reviewed Quarterly Journal on Literature, 2020)
This paper interrogates the role of the missionaries and the East India Company in the inauguration of Bengali translation and argues that translation served as an epistemological tool for conquering an alien reality and exercising discursive control over the subject people.
Keywords: Bengali; translation; Colonialism; Fort William College; William Carey; Srirampur Mission